Desain Perbandingan MPPT P&O dan IC pada Solar Sel 1500 WP Menggunakan Konverter SEPIC - Luki Septya Mahendra; Jauharotul Makmunah; Karimatun Nisa (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2021)
Electricity is a very important requirement for life. The need for electrical energy has been dependent on fossil energy, while the availability of fossil energy is decreasing along with the increasing demand for electricity in the community, especially in Siman Village, Lamongan. To overcome this problem, many sources of energy substitutes for fossil energy have been developed and researched in the form of renewable energy sources, one of which is the source of solar energy. One of the applications of solar energy utilization is a solar cell. The proposed solar cell uses Photovoltaic (PV) 1500 WP as energy conversion. PV produces power that is volatile or erratic. So it requires Maximum Power Point Tracking (MPPT) so that PV works at its optimum point. MPPT can find the greatest power from PV using the Perturb and Observe (P&O) algorithm. The converter used is a SEPIC converter which functions to increase or decrease the voltage without changing the polarity of the resulting voltage. Furthermore, the MPPT P&O is compared the results with the MPPT Incremental Conductance (IC) as a comparison of the results of the average MPPT power.